Local Intermediate Inputs and the Shared Supplier Spillovers of Foreign Direct Investment - Kee, Hiau Looi (World Bank Group, Washington, DC, 2014)
Trade liberalizations have been shown to improve domestic firms' performance through the new varieties of imported intermediate inputs. This paper uses a unique, representative sample of Bangladeshi garment firms to highlight that local intermediate inputs may also enhance domestic firms' performance, through the shared supplier spillovers of foreign direct investment (FDI) firms. An exogenous EU trade policy shock is shown to cause some FDI firms in Bangladesh to expand, which led to better performance of the domestic firms that shared their suppliers. Overall, the shared supplier spillovers of FDI explain 1/4 of the product scope expansion and 1/3 of the productivity gains within domestic firms.